Revealing the role of U2AF1 in splicing regulation and chimeric RNA dynamics - Sangeen Khan; Yue Tang; Yangyang Guo; Jing Feng; Hui Wu; Zhenguo Song; Chengjuan Zhang; Fujun Qin (Scientific Reports)
Abstract U2 small nuclear ribonucleoprotein auxiliary factor 1 (U2AF1) gene is a pivotal splicing factor frequently mutated in various malignancies, including myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML). U2AF1 plays a critical role in the recognition and processing of 3ʹ splice sites during pre-mRNA splicing, thereby contributing to the regulation of gene expression and the generation of protein diversity. However, how U2AF1 contributes to the formation and regulation of different categories of chimeric RNAs remains elusive. In this study, we aimed to elucidate the involvement of U2AF1 in chimeric RNA formation and its regulatory impact on different categories of chimeric RNA. Employing knockdown and overexpression strategies in leukemia and esophageal cancer cell lines, we conducted paired-end RNA sequencing following U2AF1 knockdown to assess transcriptomic alterations and their influence on alternative splicing patterns. Subsequently, we utilized the SOAPfuse algorithm to detect and characterize chimeric RNAs from the paired-end RNA sequencing data. Our findings unveiled significant changes in the landscape of chimeric RNA upon U2AF1 knockdown, highlighting its critical role in chimeric RNA formation. This study provides novel insights into how U2AF1 mediates chimeric RNA formation and regulates distinct categories of chimeric RNA within leukemia cell lines. Thereby highlighting its potential as a biomarker for leukemia and other malignancies, promising avenues for future diagnostic and therapeutic developments.